Agrobiodiversidade, segurança e soberania slimentar na Terra Indígena Uaçá, Oiapoque - Amapá - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
In view of the accelerated changes in world agricultural contexts, with a tendency towards monoculture, homogenization and loss of genetic variability of cultivated species, the present research had as its main objective to demonstrate the importance of indigenous people's knowledge in the conservation of agrobiodiversity and its relationship with food security and sovereignty in the Indigenous Land (IL) Uaçá, Oiapoque (AP). The research method was predominantly qualitative, through an interdisciplinary approach. The field research was carried out by means of a case study, with four field trips, two in the dry period and two in the rainy period. The case study allowed the use of interdisciplinary techniques such as: free listing, direct observation, participant observation, semi-structured interviews, document analysis, photo and video analysis. Initially, the work thesis presents an introduction and general methodology with the description of the study area and the indigenous peoples who live in the IL Uaçá. Important concepts, such as agrobiodiversity, indigenous knowledge, food security and sovereignty, are presented for discussion -in the subsequent chapters. This proposal was conceived by an indigenous researcher, based on the idea that indigenous knowledge should guide the reflections, in intersection with other knowledge, getting beyond the theoretical frameworks of western science. The data analysis indicates that the knowledge of the indigenous peoples of Oiapoque converges with the conservation of local agrobiodiversity and is expressed, above all, in symbols, rituals, artifacts, songs, food, plant cultivation, and animal management. The thesis is divided into three chapters structured as articles. In the first chapter, I describe the agricultural system of the indigenous people of the Uaçá and its material and immaterial dimensions. The second chapter, which is published in a scientific journal, discusses the relationship between agrobiodiversity and indigenous food security and sovereignty in the extreme north of the state of Amapá. In the third and final chapter, I propose a discussion on the familiarization of plant species, in dialogue with anthropological discussions on the subject, considering that the concept of domestication presented some gaps to explain the relationship of the indigenous peoples of the Uaçá with the plants, especially with the mama maiõk (wild mountain cassava). This last chapter was submitted to a scientific journal and is currently being evaluated. Among the main conclusions of the research, it became evident that the management of agrobiodiversity that the indigenous people of the Uaçá have developed over time allows them to have sustainable conditions and food sovereignty in order to survive in various environments. Furthermore, it guarantees them a balanced diet, with plenty of animal protein, collected and cultivated fruits, manioc and its derivatives, among other products of local preference, variable according to seasonality. Another relevant point is considering the “roça” (cultivation field) as an important locus of knowledge production and indigenous socialization, with multiple dimensions that strengthen social relations inside and outside the indigenous land. With this, I hope to have contributed to establishing the necessary dialogue between indigenous knowledge and scientific knowledge, in addition to strengthening the Amazonian scientific production.
Keywords: Conhecimento tradicional; Hábitos alimentares; Indígenas - Nutrição; Ecologia agrícola; Nativos - Brasil; CNPQ::OUTROS; Interdisciplinar; Conhecimentos indígenas; Conservação; Familiarização de plantas; Diversidade agrícola